The Epstein–Barr virus DNA load in the peripheral blood of transplant recipients does not accurately reflect the burden of infected cells. (5th November 2016) - Fink, Susanne; Tsai, Ming‐Han; Schnitzler, Paul; Zeier, Martin; Dreger, Peter; Wuchter, Patrick; Bulut, Olcay C.; Behrends, Uta; Delecluse, Henri‐Jacques
Summary: Transplant recipients frequently exhibit an increased Epstein–Barr virus (EBV) load in the peripheral blood. Here, we quantitated the EBV‐infected cells in the peripheral blood of these patients and defined the mode of viral infection, latent or lytic. These data indicated that there is no strong correlation between the number of infected cells and the EBV load (EBVL). This can be explained by a highly variable number of EBV copies per infected cell and by lytic replication in some cells. The plasma of these patients did not contain any free infectious viruses, but contained nevertheless EBV DNA, sometimes in large amounts, that probably originates from cell debris and contributed to the total EBVL. Some of the investigated samples carried a highly variable number of infected cells in active latency, characterized by an expression of the Epstein–Barr nuclear antigens (EBNA2) protein. However, a third of the samples expressed neither EBNA2 nor lytic proteins. Patients with an increased EBVL represent a heterogeneous group of patients whose infection cannot be characterized by this method alone. Precise characterization of the origin of an increased EBVL, in particular, in terms of the number of EBV‐infected cells, requires additional investigations including the number of EBV‐encoded small RNA‐positive cells.